2002
DOI: 10.1152/japplphysiol.00981.2001
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen attenuates the cardiovascular and ventilatory responses to central command in cats

Abstract: . Estrogen attenuates the cardiovascular and ventilatory responses to central command in cats. J Appl Physiol 92: 1635-1641, 2002; 10.1152/japplphysiol.00981. 2001.-Static exercise is well known to increase heart rate, arterial blood pressure, and ventilation. These increases appear to be less in women than in men, a difference that has been attributed to an effect of estrogen on neuronal function. In decerebrate male cats, we examined the effect of estrogen (17␤-estradiol; 0.001, 0.01, 0.1, and 1.0 g/kg iv) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 34 publications
2
17
1
1
Order By: Relevance
“…3). One possible reason for the discrepancy between the Hayes et al (2002) study and the present study is related to the differences in experimental design. Their experiment dramatically increased the concentration of estrogen over a short of time by giving it to the male cats as a bolus.…”
Section: Effect Of Menstrual Cyclecontrasting
confidence: 77%
See 2 more Smart Citations
“…3). One possible reason for the discrepancy between the Hayes et al (2002) study and the present study is related to the differences in experimental design. Their experiment dramatically increased the concentration of estrogen over a short of time by giving it to the male cats as a bolus.…”
Section: Effect Of Menstrual Cyclecontrasting
confidence: 77%
“…It is considered that brief voluntary exercise mobilizes not only peripheral reflex but also central command and that brief passive movement is a form of movement in which peripheral reflex functions almost exclusively (Miyamura et al 1992;Ishida et al 2000). Recently, Hayes et al (2002) administered estrogen (17b-estradiol) to decerebrate male cats and examined the cardiovascular and ventilatory responses while stimulating parts related to central command and peripheral reflex for 60 s every 15 min. They reported that estrogen attenuated these responses to central command but not to peripheral reflex.…”
Section: Effect Of Menstrual Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence suggests that estrogen can attenuate both central command and the exercise pressor reflex (Ebert et al, 1992; Ettinger et al, 1998; Hayes et al, 2002; Schmitt et al, 2003), which as indicated above, are key contributors to ABR resetting during exercise. Given these findings, we investigated whether sex and/or physiological fluctuations in ovarian hormone concentration could modulate ABR resetting and function during dynamic exercise (Kim et al, 2012).…”
Section: Sex Ovarian Hormones and Abr Function During Exercisementioning
confidence: 97%
“…Women had a mean menstrual cycle length of 29 Ϯ 2 days, which was identified prior to studies. For experimental protocol 2 (Menstrual cycle and CBR resetting and function during exercise), 10 of the women who participated in protocol 1 were also studied during two additional phases of their menstrual cycle, late follicular (LF, days 10 -12) and midluteal (ML, days [22][23][24][25][26]. These participants were asked to use a ClearblueR Easy ovulation self test kit between days 9 and 15 of the menstrual cycle to detect the surge of luteinizing hormone in urine and more accurately identify the LF phase.…”
Section: Subjectsmentioning
confidence: 99%